Conformable Fourier Transform on Time Scales - Georgiev, Svetlin; Thange, Tukaram; Chhatraband, Sneha (Armenian Journal of Mathematics, 2025)
In this paper, we formulate the conformable Fourier transform on time scales, drawing motivation from the structure of the conformable bilateral Laplace transform. Some of the elementary properties are proved, including shifting, transform of derivative, conjugation, transform of Hilger delta function, and transform of integral.